Vascular aging mediates the association between atherogenic lipid profiles and depression: survey-weighted evidence from NHANES 2005-2020 - Liu, Ya; Zhang, Hanyue; Halimulati, Mairepaiti; Peng, Lei (Journal of affective disorders, 2026)
Background - Dyslipidemia and depressive symptoms often co-occur, but the pathway linking atherogenic lipids to mood is unclear. Vascular aging, indexed by aortic stiffness, may mediate this relationship. - Methods - We analyzed nine cycles of the National Health and Nutrition Examination Survey (2005-2020). Adults ≥20 years with complete data on lipids, estimated pulse-wave velocity (ePWV), and the Patient Health Questionnaire-9 (PHQ-9) were included (n = 17,599). Exposures were the atherogenic index of plasma (AIP), triglyceride-to-HDL-cholesterol ratio (TG/HDL-C), and HDL cholesterol. The mediator was ePWV, and the outcome was moderate-to-severe depressive symptoms (PHQ-9 ≥ 10). Survey-weighted regression and mediation models with 5000 bootstraps adjusted for sociodemographic, lifestyle, and clinical covariates. - Results - Overall, 8.7 % had moderate-to-severe depressive symptoms. Higher AIP and TG/HDL-C were associated with greater odds of depression (per SD AIP: adjusted odds ratio [OR], 1.59; 95 % CI, 1.30-1.97; per unit TG/HDL-C: OR, 1.04; 95 % CI, 1.03-1.05), while HDL cholesterol showed inverse association (per mg/dL: adjusted odds ratio [OR], 0.98; 95 % CI, 0.97-0.99). AIP was positively related to ePWV (β, 0.43 m/s; 95 % CI, 0.30-0.56). ePWV was independently associated with depression (OR per 1 m/s, 1.11; 95 % CI, 1.06-1.16). Mediation indicated that ePWV explained 10.4 % of the AIP-depression association, 8.2 % for TG/HDL-C, and 6.4 % for HDL cholesterol in overall study population. Mediation occurred in both sexes, with larger proportions mediated in women. - Conclusions - Atherogenic lipid phenotypes were linked to depressive symptoms, with vascular aging explaining part of this association, especially in women. These findings support vascular aging as a pathway connecting dyslipidemia to mood and motivate longitudinal studies targeting lipid quality and large-artery stiffness.
Online verfügbar: 24. November 2025, Artikelversion: 28. November 2025
Gesehen am 27.02.2026